Evaluation study of solar powered public street lighting as battery charging at Islamic Center based on PSIM - Wina, Cut; Muhammad, Muhammad; Mahmudi, Irwan (Journal Geuthee of Engineering and Energy, 2024)
Electrical energy is essential for the growth and advancement of technological knowledge that continues to increase. Solar cells are devices that convert solar energy through photovoltaic devices. Solar cell public street lighting (PJUBS) uses unlimited and free solar energy, is a feasible and cheap alternative to providing electric lighting. The Islamic center mosque is one of the places of worship for the majority of Muslims in the city of Lhokseumawe using public street lighting to support public security and safety. Installation of lamps for lighting is installed at several points, namely right, left or in the middle of the road, as needed, including flyovers, underpasses, and bridges. Public street lighting that is efficient and environmentally friendly is in accordance with SNI 7391: 2008. In this study, the lamps used in this evaluation study are solar types with a power of 50 Watts. The calculation results show that the illumination produced at the end of the road when using a 50 Watt solar LED lamp is 0.29 lux so that this does not comply with the provisions of BSN SNI 7391: 2008. This condition is influenced by several factors, namely surface temperature, shadows, inclination angle, light intensity, irradiation, and the condition of the panel surface in order to maximize the conversion value of sunlight into electrical energy